Lactiplantibacillus plantarum IS-10506 Supplementation Improves Clinical Outcome and Immunology Markers in Psoriasis Vulgaris Patients: A Randomized Controlled Trial - Umborowati, Menul Ayu; Hasna, Iffa Halimah; Endaryanto, Anang; Surono, Ingrid Suryanti; Prakoeswa, Cita Rosita Sigit (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Probiotics may modify the gut microbiome and have been proven to improve psoriasis vulgaris. Lactiplantibacillus plantarum IS-10506 is a probiotic strain of Indonesian origin. It offers a safe and effective probiotic for psoriasis patients in Indonesia. This study was conducted to evaluate the effect of L. plantarum IS-10506 on clinical and immunology markers in psoriasis vulgaris.METHODS: This randomized, placebo-controlled, and double-blind trial compared L. plantarum IS-10506 (2×1010 CFU/day) and placebo in 49 patients mild-moderate psoriasis vulgaris, which were divided into intervention (n=24) and control groups (n=25). The interventions were given twice daily for 12 weeks. Both groups received topical corticosteroid and emollient as standard treatment. Psoriasis area and severity index (PASI), dermatology life quality index (DLQI), interleukin (IL)-10, IL-17, and forkhead box protein (Foxp3) were then assessed.RESULTS: Mean PASI score for the the subjects in probiotic group was significantly reduced compared to placebo at week-6 (p=0.024), and was sustained until week-12 (p=0.049). At week-12, DLQI scores in the probiotic group were lower than placebo (7.57±5.77 vs. 7.79±5.48). IL-17 level was significantly decreased (p=0.013), while the IL-10 and Foxp3 were significantly increased (p≤0.001 and p=0.048, respectively) in probiotic group. Six months after the completion of study, subjects in probiotic group had a lower probability of flares (52.2%) compared to placebo (79.2%). Two subjects receiving probiotics and one receiving placebo noticed changes in defecation frequency, while another subject in the placebo group complained of mild nausea.CONCLUSION: L. plantarum IS-10506 might effectively improve clinical outcomes and immune biomarkers in psoriasis vulgaris patients, potentially acting as an adjuvant therapy.KEYWORDS: psoriasis, probiotic, clinical severity, immune marker, human and health